2022
DOI: 10.1038/s41467-022-35185-6
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide geospatial analysis of county racial and ethnic composition and public drinking water arsenic and uranium

Abstract: There is no safe level of exposure to inorganic arsenic or uranium, yet recent studies identified sociodemographic and regional inequalities in concentrations of these frequently detected contaminants in public water systems across the US. We analyze the county-level association between racial/ethnic composition and public water arsenic and uranium concentrations from 2000–2011 using geospatial models. We find that higher proportions of Hispanic/Latino and American Indian/Alaskan Native residents are associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…Arsenic and uranium occur naturally in the environment and often are not completely removed during public-supply drinking-water treatment processes. 107 Adverse health effects associated with uranium and lead in drinking water have been well documented. Recent studies have linked drinking water uranium exposure to osteotoxicity 108 and nephrotoxicity 109 in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Arsenic and uranium occur naturally in the environment and often are not completely removed during public-supply drinking-water treatment processes. 107 Adverse health effects associated with uranium and lead in drinking water have been well documented. Recent studies have linked drinking water uranium exposure to osteotoxicity 108 and nephrotoxicity 109 in humans.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of higher concentrations of Ca 2+ (10 mM) and PO 4 3− (2 mM) reached supersaturation with respect to HAp at pH values ranging from 7.0 to 11.0. The gradual removal of aqueous arsenate in solutions (Figure 2F,H) was observed after white Ca−P precipitates started to form.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In addition to air pollution, Hispanic communities—along with other people of color—are also more likely to be exposed to drinking water contaminants, such as uranium, chromium, and arsenic. 40 42 Both cadmium and arsenic have been linked to kidney disease, 43 a health condition for which Hispanic individuals (particularly those from Puerto Rico 44 ) have worse outcomes than non-Hispanic White people. 45 , 46 Navas-Acien, along with lead author Anne Nigra, an assistant professor at Columbia University, recently showed that U.S. community water systems serving semi-urban areas with higher Hispanic populations were the most likely to exceed the U.S. Environmental Protection Agency maximum contaminant level for arsenic, even as other systems were actively working to reduce arsenic levels.…”
Section: Research On Hispanic Populationsmentioning
confidence: 99%
“… 41 Their latest study, which examined metals in drinking water at the county population level, further demonstrates the exposure disparities that Hispanic communities face. 40 …”
Section: Research On Hispanic Populationsmentioning
confidence: 99%